2004
DOI: 10.1111/j.1365-2249.2004.02592.x
|View full text |Cite
|
Sign up to set email alerts
|

Human endogenous retroviruses: transposable elements with potential?

Abstract: SUMMARYHuman endogenous retroviruses (HERVs) are a significant component of a wider family of retroelements that constitute part of the human genome. These viruses, perhaps representative of previous exogenous retroviral infection, have been integrated and passed through successive generations within the germ line. The retention of HERVs and isolated elements, such as long-terminal repeats, could have the potential to harm. In this review we describe HERVs within the context of the family of known transposable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
74
0
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(78 citation statements)
references
References 76 publications
0
74
0
1
Order By: Relevance
“…HERVs possess two long-terminal repeats that flank a region containing group-specific Ag (gag), polymerase and other enzymes, and envelope (env) genes and no longer make virions due to inactivating mutations accumulated through evolution. HERVs are believed to have arisen from retroviruses that integrated into the genome of an ancestral germline (6). Located on the first chromosome HERV-K18 (1q23.1-q24) sits on the first intron of the cellular gene CD48 and has an opposite direction of transcription to that gene (7).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…HERVs possess two long-terminal repeats that flank a region containing group-specific Ag (gag), polymerase and other enzymes, and envelope (env) genes and no longer make virions due to inactivating mutations accumulated through evolution. HERVs are believed to have arisen from retroviruses that integrated into the genome of an ancestral germline (6). Located on the first chromosome HERV-K18 (1q23.1-q24) sits on the first intron of the cellular gene CD48 and has an opposite direction of transcription to that gene (7).…”
mentioning
confidence: 99%
“…HERV-K18 belongs to a class of retroelements, HERVs, that retain much of the genomic organization of modern day exogenous retroviruses such as HIV (6). HERVs possess two long-terminal repeats that flank a region containing group-specific Ag (gag), polymerase and other enzymes, and envelope (env) genes and no longer make virions due to inactivating mutations accumulated through evolution.…”
mentioning
confidence: 99%
“…The etiology is unknown, although possible causes include viral triggers 1 . The latter may include human endogenous retroviral (HERV) families: HERV-K, HERV-L, ERV-9, and ERV-3 2,3 .…”
Section: To the Editormentioning
confidence: 99%
“…Increasing evidence shows links of HERVs with some human diseases, such as male infertility, schizophrenia, and cancer [6,[10][11]16]. Several studies reported expression of one or more HERVs in physiological or pathological conditions, in one or more body sites.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, similar to other animal species, the human genome contains remnants of many different kinds of retroviruses that are now endogenously transmitted and are hence called human endogenous retroviruses (HERVs) [4][5][6][7][8]. Apart from ~3% of coding sequences, for an estimate of 20,000-25,000 genes [9], the vast majority of DNA is composed of introns, pseudogenes, duplications, and by at least 50% repeat sequences (including genes that encode ribosomal components, minisatellite DNA, HERVs, and probably much more) [6,9,[10][11]. HERVs are grouped in 26-31 independently acquired families or lineages [12][13].…”
Section: Introductionmentioning
confidence: 99%